2016
DOI: 10.1530/joe-16-0117
|View full text |Cite
|
Sign up to set email alerts
|

Potential benefits of melatonin in organ transplantation: a review

Abstract: Organ transplantation is a useful therapeutic tool for patients with end-stage organ failure; however, graft rejection is a major obstacle in terms of a successful treatment. Rejection is usually a consequence of a complex immunological and nonimmunological antigen-independent cascade of events, including free radical-mediated ischemia-reperfusion injury (IRI). To reduce the frequency of this outcome, continuing improvements in the efficacy of antirejection drugs are a top priority to enhance the long-term sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 188 publications
0
35
0
Order By: Relevance
“…Melatonin is an indoleamine produced mainly by the pineal gland and it has a potent free radical scavenger activity with subsequent antioxidant and antiapoptotic functions (Esteban‐Zubero et al., ). Among the known antioxidants, melatonin has high efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Melatonin is an indoleamine produced mainly by the pineal gland and it has a potent free radical scavenger activity with subsequent antioxidant and antiapoptotic functions (Esteban‐Zubero et al., ). Among the known antioxidants, melatonin has high efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Although melatonin was fi rst considered to solely be a circadian cycle regulator, several studies have shown that it is effective as a free radical scavenger and antioxidant agent. In addition to the regulation of circadian biology, melatonin has also been shown to modulate several molecular pathways of infl ammation, oxidative stress, and cellular injury and have vasorelaxant and anti-fi brotic properties (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the allied processes utilized by melatonin to reduce these catastrophic effects, e.g., indiscriminate molecular destruction which ultimately leads to cellular apoptosis, include improving the efficacy of the mitochondria respiratory complexes [129,183,184], enriching ATP production [185,186], reducing free radical generation by limiting electron leakage, commonly referred to as radical avoidance [128], upregulating antioxidative enzymes [187,188], stimulating glutathione synthesis [189,190], direct radical detoxification [103,191] and probably yet to be defined means. The outcome of these combined actions is the preservation of cellular and organ physiology, as well as the prevention of organismal death, by mitigating cellular loss due to apoptosis [167,192,193,194,195].…”
Section: Intrinsic Sources Of Melatoninmentioning
confidence: 99%